The Effect of Physical Activity on Adolescent Mental Health - Amir, Eka Fitri; Fitriani, Fitriani; Pinta, Aisyah (Ahmar Metastasis Health Journal, 2024)
Adolescence is one of the human phases where maximum growth and development occurs in daily life so that it is possible to cause uncontrolled emotional problems, including anxiety, fear, insecurity, trauma which ultimately affects the mental health of teenagers. Various factors that cause mental imbalance responses are external factors originating from the environment or pressure resulting from life choices chosen by adolescents. This research aims to determine the description of physical activity and mental health in adolescents who are entering a period of adjustment in a new environment at a university in the Batam city. This research uses a cross sectional approach with quantitative methods. The sampling technique is random sampling by distributing questionnaires to respondents containing personal data and physical activity using GPAQ and mental health using the DASS-21 questionnaire which has been tested for validity first. The respondents in this research were 121 first semester students from several universities in Batam City. The research results showed that there was no relationship between physical activity and anxiety, namely 0.714 (P Value > 0.05). Based on the results of this study, it was concluded that physical activity has no correlation between anxiety.